Synthesis and Structural Analysis of New (−)-Cytisine Squaramides - Anna K. Przybył; Jan Janczak; Adam Huczyński (Molecules)
Derivatives of squaric acid are valuable building blocks with promising applications in the investigation of various bioactivities. In this study, we focus on squaramides functionalized with the (−)-cytisine moiety, an alkaloid known for its bioactivity as a nicotinic acetylcholine receptor agonist and its application in nicotine addiction treatment. Reactions of cytisine-monosquarate with several amines, such as ammonia, propargylamine, and morpholine, led to the formation of novel conjugates of cytisine-squaramides. Additionally, squaramide containing two cytisine moieties was synthesized via the reaction of diethyl squarate with cytisine at a 1:2 molar ratio. All obtained squaramides were thoroughly characterized by MS, FT-IR, and NMR methods and by single-crystal X-ray diffraction analysis. To gain deeper insights into their structural properties and intermolecular interactions, geometry optimizations were performed using DFT calculations, complemented with 3D molecular electrostatic potential maps.